Children's Rights In The Book Of Tarbiyah Al-Aulad Fi Al-Islam By Sheikh Muhammad Mutawalli Al-Sya‘Rawi - Aldiansyah, Aldiansyah; OK, Azizah Hanum; Arsyad, Junaidi (Journal of Educational Sciences, 2025)
This study aims to analyze the Rights of Children in the Book of Tarbiyah al-Aulād Fī al-Islām by Sheikh Muḥammad Mutawallī al-Sya‘rāwī. This research method uses qualitative research with the type of manuscript study research. Technical data analysis using content analysis. The overall results of the study there are 22 points of children's rights in the family then classified/grouped into two (2) points. The points of children's rights before birth are four, the piety of parents, the physical health of both parents from disease, asking for protection from Allah from Satan before having sex with his wife, not attacking her (aborting) while she is still in her mother's womb. The points of children's rights after birth are eighteen, the Adhan in his right ear, shaving the hair of a newborn baby and giving charity with the weight of his hair, Sacrifice (aqiqah) for them on the seventh day after birth, raising faith before the Koran, teaching the Koran, Commandment for prayer, Encouraging them to seek knowledge, Providing for them, Separating children in bed, Education of children, Honoring children and doing good to them, leaving prayers for them, Prohibition of bad associations, and justice between them.